A Virtual Curriculum to Prepare Medical Students to Achieve Accreditation Council for Graduate Medical Education Level-1 Milestones in Orthopaedic Surgery. Issue 1 (January 2021) - Morley, Meghan; Kellish, Alec S.; Fleischer, Lindsay; Clements, David; Freeland, Erik; Ramirez, Rey; Fedorka, Catherine; Gutowski, Christina; Pollard, Mark; Kim, Tae Won; Kleiner, Matthew T.
Abstract : Abstract: As a part of the American healthcare system's response to the Coronavirus Disease 2019 (COVID-19) global pandemic, the Association of American Medical Colleges recommended that medical schools temporarily remove students from clinical settings and transition to an entirely online learning environment. This posed an unprecedented challenge to students in the clinical years of their medical education. To address this unexpected shift, we modified an in-person workshop to teach orthopaedic trauma basics to 5-week virtual course for third year medical students from several schools in New Jersey and Pennsylvania. We focused on moving students toward the Level-1 milestones for basic fracture care with a combination of weekly lectures and virtual interactive small group sessions, all conducted via WebEx and proctored by an orthopaedic attending or resident. The course was well received by students. Participation in the course was completely voluntary and did not count for credit at any institution. The course was valuable to students because the students who registered chose to fully complete the 5-week course and no student missed more than one small group session. On a postcourse survey, 100% of students said they would be highly likely to recommend the course to a future student, and the average rating for educational value of the course was 4.98 of 5. Given the current limitations in clinical education because of the COVID-19 pandemic, our course provides a reasonable alternative to clinical experience and prepares students with the knowledge and many of the skills that are required to succeed as orthopaedic interns. Furthermore, the success of our course this year suggests that similar programing may be a useful adjunct to clinical experiences even when it is safe to return to more traditional medical school scheduling.